IMPLEMENTASI PENANGANAN KETERLAMBATAN PENERBANGAN DI BANDARA INTERNASIONAL SULTAN SYARIF KASIM II KOTA PEKANBARU - Apriana "; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
In this times, high mobility is needed to move from one area to another in a short time. Therefore, an effective and efficient transportation is needed like aircraft. Implementation handling delay management at Sultan Syarif Kasim II International Airport Pekanbaru based on the Republic of Indonesia's Minister of Transportation Regulation No.89 of 2015 still not running optimally, because passengers who get delay’s flight still haven’t received specific information regarding the reasons for the delay and haven’t received compensation according to what has been determined, and not all boarding gate officers able to provide information of delay to passenger. The goals of this study are to find out and analyze the implementation and factors that inhibit handling delay management at Sultan Syarif Kasim II International Airport in Pekanbaru. This study uses the Ripley and Franklin theory concepts (Tahir, 2015) where there are three things that can measure the success of implementing a policy, that are the loyalty of bureaucracy level (compliance), have a smooth routine and there is no problems, and performance. This research method is descriptive qualitative using purposive sampling with data collection techniques through observation, documentation, interviews, and literature. The results of this study indicate that implementation handling delay management has been running but has not been optimally implemented. It can be proof with the delay filghts that dont provide an information reasons for delays, dont provide compensation according to the established policies and passengers also dont really know and understand about the policy. Keywords : Implementation, Minister Regulation, Flight Delay.